Coronary Artery Aneurysm Post Drug-Coated Balloon Angioplasty - Aninka Saboe, MD; Chetan Upadhya, MD; Aloke Finn, MD; Sandeep Basavarajaiah, MD (JACC: Case Reports)
Drug-coated balloons have emerged as effective therapy for treating in-stent restenosis and de novo lesions. The animal studies have shown the mechanism of action of paclitaxel-coated balloon in coronary arteries which leads to medial necrosis that may explain the better angiographic remodelling observed with paclitaxel- as compared to sirolimus-coated balloons. However, in some cases, paclitaxel may cause adverse remodelling resulting in coronary artery aneurysm. Here, we report 4 cases of coronary artery aneurysm post paclitaxel-coated balloon angioplasty and discuss its possible mechanism, management, and potential implications for future practice.